3D Printing of Hierarchical Porous Silica and α‐Quartz. Issue 7 (18th May 2018) - Putz, Florian; Scherer, Sebastian; Ober, Michael; Morak, Roland; Paris, Oskar; Hüsing, Nicola
Abstract: The ability to macroscopically shape highly porous oxide materials while concomitantly tailoring the porous network structure as desired by simple and environmentally friendly processes is of great importance in many fields. Here, a purely aqueous printing process toward deliberately shaped, hierarchically organized amorphous silica and the corresponding polycrystalline quartz analogues based on a direct ink writing process (DIW) is presented. The key to success is the careful development of the sol–gel ink, which is based on an acidic aqueous sol of a glycolated silane and structure‐directing agents. The resulting 3D (DIW) printed silica consists of a macroporous network of struts comprising hexagonally arranged mesopores on a 2D hexagonal lattice. Together with a printed porous superstructure on the millimeter scale, well‐defined pore sizes and shapes on at least three hierarchy levels can thus be fabricated. The introduction of devitrifying agents in the printed green part and subsequent heat treatment allows for the transformation of the silica structure into polycrystalline α‐quartz. While small pores (micro‐ and mesopores below 10 nm) are lost, the printed morphology and the macroporous network of struts is preserved during crystallization. Abstract : 3D printed hierarchical porous silica superstructures on the millimeter scale with well‐defined pore sizes and shapes on at least three hierarchy levels are fabricated via direct ink writing of a carefully developed sol–gel ink. Crystallization of these structures leads to polycrystalline α‐quartz with the same macroscopic shape and morphology of the cellular strut network.